소나무 인공교배 차대집단에서 Microsatellite marker 혈통분석을 이용한 인공교배 효율 및 관리상태 평가 - 여태림; Tae-lim Yeo; 김지훈; Jihun Kim; 이다영; Dayoung Lee; 강규석; Kyu-suk Kang (한국산림과학회지, 2023)
임목육종에 있어 인공교배는 매우 중요한 방법 가운데 하나이다. 인공교배를 이용하면 유용한 유전자형을 생성하고 빠르게 개량효과를 증진시킬 수 있다. 그러나 그 동안 소나무(Pinus densiflora) 육종프로그램의 인공교배 효율이나 성공률에 대한 평가는 미흡하였다. 인공교배 효율 및 차대 육종집단 관리 평가를 위해 2015년에 조성된 소나무 충북2호×강원40호, 강원40호×충북2호 집단 159개체를 사용하였다. 차대묘의 microsatellite 유전자형을 식별한 뒤, 연구에 이용된 프라이머 수의 적절성 평가와 혈통분석을 진행했다. 프라이머 수는 차대묘 개체들을 구분하는데 적절했다고 판단되었고 159개 차대묘 중 60개체가 친자 혈통(충북2호와 강원40호의 교배에 의한 차대)으로 식별되었다. 또한, 육종집단 관리상의 문제가 의심되는 결과가 나타난 54개의 차대묘를 제외하고 다시 혈통분석을 진행했다. 두 번째 분석에서는 105개 차대묘 중 47개체가 친자 혈통(충북2호와 강원40호의 교배에 의한 차대)으로 식별되었다. 결론적으로, 임목육종 프로그램에서 인공교배의 효율을 향상시키기 위해서 여러 주의사항이 요구된다. 먼저, 모수와 화분수의 정확한 클론명 식별이 이루어져야 한다. 암구과의 격리, 인공교배 시기의 결정 등 인공교배 과정이 잘 수행되어야 하며 교배 후 차대묘 관리 모니터링도 필요하다. 이 때 모수, 화분수의 식별과 교잡 사후관리 모니터링 과정에 분자표지자를 이용하는 것이 바람직하다. 본 연구결과는 앞으로 소나무류 육종프로그램에 있어 인공교배에 대한 참고 정보를 제공할 것이다. Controlled pollination (CP) is an important method in tree breeding programs because CP quickly generates desirable genotypes and rapidly maximizes genetic gains. However, few studies have evaluated the efficiency and success rate of CP in the breeding program of Pinus densiflora. To evaluate CP and the management of control pollinated progenies, we used 159 individuals in CB2 × KW40 or KW40 × CB2 populations that were established in 2015. After genotyping microsatellite loci, we estimated whether the number of primers was sufficient or not. Then, we performed pedigree analysis. The result showed that the number of primers was sufficient. By pedigree analysis, we found out that 60 of 159 individuals had been generated by the mating between CB2 and KW40. In the maternity analysis, there was evidence to indicate the possibility of management problems. Therefore, we excluded 54 individuals and repeated the pedigree analysis. In the second analysis, 47 of 105 individuals were generated by the mating between CB2 and KW40. To increase the efficiency of CP in tree breeding programs, several precautions are required. It is necessary to identify the exact clone names of the mother and father trees. In addition, CP processes should be performed properly, including deciding on the schedule of CP and the isolation of female strobili or flowers. Finally, the monitoring of hybrid progenies management after mating is important. Molecular markers should be used to identify the clone names of the mother and father trees and for monitoring post hoc management. This study provides a reference for tree breeding programs for the future control pollination of pine species.